Predictive Value of Systemic Immune Inflammation Index for Postoperative Atrial Fibrillation in Patients Undergoing Isolated Coronary Artery Bypass Grafting - Murat Selçuk; Tufan Çınar; Faysal Şaylık; Selami Doğan; Ismail Selçuk; Ahmet L. Orhan (Medeniyet Medical Journal)
Objective: Inflammation plays an important role in the initiation of postoperative atrial fibrillation (PoAF) in individuals undergoing cardiac surgery, Thus, this study aimed to investigate the predictive value of the systemic immune inflammation index (SII) to develop PoAF in such patients. Methods: In total, 391 consecutive patients undergoing an isolated coronary artery bypass grafting (CABG) were retrospectively analyzed. PoAF was defined according to the current guideline. The SII is determined using the following equation: neutrophil (N) × platelet (P) ÷ lymphocyte (L). Results: The incidence of PoAF in the present study was 24% (n=97 cases). Multivariate logistic regression analysis revealed that the SII was an independent predictor of PoAF (Odds ratio: 1.002 95% confidence interval: (1.001-1.002), p<0.01). The optimal value of the SII in detecting PoAF was established by a receiver operating characteristic curve assessment, and it was >807.8 with 60.8% sensitivity and 80.9% specificity [area under the curve (AUC): 0.7107]. The AUC value of SII in detecting PoAF was much greater than the AUC values of both the neutrophil to lymphocyte ratio (NLR) and the platelet to lymphocyte ratio (PLR) (AUC: 0.6740 and AUC: 0.6426, respectively). Conclusions: This study revealed that SII was an independent predictor of PoAF in patients who were operated on for isolated CABG. Additionally, SII had a better discriminative ability for PoAF compared to either NLR or PLR among these cases.